A Look at The History of Translations of Alisher Navoi's Works into Karakalpak - Azilova Zuhra Gulmon qizi (Genius Journals, 2022)
The article discusses the impact of Alisher Navoi's work on Karakalpak literature, the study and translation of his works.
Keywords: Translation studies; literary translation; manuscripts; poems